PEMBUATAN VIRTUAL TOUR GUIDE KABUPATEN TRENGGALEK MENGGUNAKAN METODE TRACING MAP - Prambudi, Aditya Risan; Retnowati, Nurcahyani Dewi (Compiler, 2014)
Making of Trenggalek district Virtual Tour Guide Using Tracing Map Method is one of some solution to introduce tourism object and become guide for touristwho want to visit Trenggalek’s tourism place.Making of Trenggalek districtVirtual Tour Guide application integrating between adobe flash CS5.5’s design and action script 3 programming. Making of Trenggalek district Virtual Tour Guide application can use as one of some choice to get tourism information besides map and tourism’s coventional guide book.Based on a survey of 30 correspondents, the results showed that 55.33% of applications considered good, 32.67% stated that this application is quite good, 10% said very good and, 2% were less well expressed.